The Effects of Hedonism and Gender on Liberal Accounting - Eko Widodo Lo (Telaah Bisnis, 2021)
This study investigates the influence of hedonism and gender on liberal accounting actions. This research uses a survey method by using questionnaires. Factor analysis results reveal that three questions of hedonism and four questions of liberal accounting are valid. Cronbach’s alpha of each variable show that they are reliable. Multiple regression analysis is conducted for examining the research hypotheses. Control variables in the research model are job and education level. Data analysis results indicate that hedonism positively affects liberal accounting. However, the results show that gender does not affect liberal accounting. The research contribution is to relate hedonism and gender with liberal accounting behaviors. This provides new theoretical explanations of liberal accounting behaviors. Study conclusions can be beneficial for deciding the appropriate human characteristics for certain accounting choices.